EXPLORING COGNITIVE CONTROL PROCESSES OF YOUNG ADULTS IN MULTITASKING ACTIVITIES: A SCIENTIFIC PERSPECTIVE - Aziz, Indah Al; Fathia, Vitriza Naila; Dahlan, Tina Hayati; Habib, Muhammad Akmal (Universitas Pakuan, 2024)
Doing multiple activities at the same time is something that most people are familiar with. Therefore, the cognitive control process is an important cognitive mechanism in regulating and controlling human mental activity. This process involves the ability to process information, allocate cognitive resources, control attention, and make decisions. This research is a cognitive science study conducted through a simulation involving three young adults at a university in Bandung as participants. Each participant followed a structured simulation with the same rules. In an effort to collect data, the researcher collected data using a journaling method with self-report technique. This study aims to analyze the picture that occurs from the cognitive process in response to young adults multitasking activities. The cognitive control process has benefits to help individuals in doing several tasks at the same time so that it will save time and make activities run more effectively. Based on the results of this study, it was found that almost all young adults described complicated cognitive processes in multitasking activities and had difficulty completing the activity objectives to the fullest. However, through cognitive control, it was found that two subjects were finally able to complete the task by choosing one of the activities that should be done quickly and accurately in their thought process.